Potencials of sap flow evaluation by means of acoustic emission measurements - Michal Černý; Pavel Mazal; Jan Čermák; Libor Nohal (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
The work deals with measurement techniques of water conducting system in the trees. Water conducting system (including xylem and phloem) indicates its importance for related physiological processes. There are still problems how to measure its functioning (which variables and how), especially in the open field (e.g., forests and orchards) in order to get maximum information about it. Simple band dendrometers measuring seasonal dynamics of stem growth have been already applied for many years, being gradually replaced by their more sophisticated electronic versions most recently. The sap flow is a suitable variable, because it links roots and crowns and provide information about transporting the largest amount of mass in plants, which can be decisive for their behavior. Following pioneering work in the last century (Huber, 1932), many types of sap flow measurement methods based on a variety of principles (e.g., thermodynamic, electric, magneto-hydrodynamic, nuclear magnetic resonance, etc.) have been described. Only a few of these, particularly those based on thermodynamics, have been widely used in field-grown trees. E.g., heat pulse velocity system developed by Green (1998) and Cohen et al. (1981). Heat ratio method also works with pulses, but interpreted the data in more sophisticated way (Burgess, 2001). Widely used is a simple heat-dissipation method (Granier, 1985). Direct electric heating and internal sensing of temperature was applied in the trunk heat balance method (Čermák et al., 1973, 1976, 1982, 2004; Kučera et al., 1977; Tatarinov et al., 2005). The heat field deformation method is based on measurement of the deformation of the heat field around a needle-like linear heater (Nadezhdina et al., 1998, 2002, 2006; Čermák et al., 2004).Another important variable is water potential, which could be measured in the past only periodically on selected pieces of plant material using pressure (Scholander) bomb, but most recently also continuous measurements became possible due to application of psychrometric method (Dixon and Tyree, 1985). There exist also other physical variables carrying important information, which can be measured using different principles. This includes e.g., acoustic methods, which can detect quantitative variation of pulses occurring during cavitation events, associated with interruptions of water columns in vessels. This must not necessarily be a single source of acoustic emissions. In this study we are focused on a general description of acoustic events measurable in a wide range of their spectrum. The first aim was to detect such signals and the second to learn them and gradually analyze in order to better understand the associated processes causing their occurrence and their relations to plant life.